Nyelimut Dance Performance as An Expression of Ogan Tribe Culture in Ogan Komering Ulu Regency - Astuti Wahyuningsih, Dwi; Hartono, Hartono; Sumaryanto Florentinus, Totok (Catharsis, 2020)
Nyelimut dance is a characteristic of the Malay culture of South Sumatra, which was created based on the cultural spirit of the Ogan tribe who resides on the banks of the Ogan river, OKU Regency. Nyelimut dance is an adaptation of the Nyelimut tradition that was held when the Komering tribal wedding custom was held, Nyelimut tradition was performed after the covenant event that symbolizes the love of parents towards their children. The problem raised in this study aims to analyze the cultural expressions contained in the form of Nyelimut dance performances. The approach used is a qualitative method with a case study research design. Data collection techniques include observation, interview and document study. The results showed that the performance elements contained in the Nyelimut dance show some form of behavior that leads to goodness in social life. The moral message to be conveyed through Nyelimut dance is clearly seen in several movements arranged in Nyelimut dance. Then, Nyelimut dance performance form which consists of several dance elements namely elements of dance moves, space, property, accompaniment, make-up, fashion, and audience become a unified whole so as to create a good art performance and certainly reflect the local culture of the Ogan people who reside in OKU Regency.